MATES in Construction: Impact of a Multimodal, Community-Based Program for Suicide Prevention in the Construction Industry - Gullestrup, Jorgen (Molecular Diversity Preservation International (MDPI), 2011)
A large-scale workplace-based suicide prevention and early intervention program was delivered to over 9,000 construction workers on building sites across Queensland. Intervention components included universal General Awareness Training (GAT; general mental health with a focus on suicide prevention); gatekeeper training provided to construction worker volunteer ‘Connectors’; Suicide First Aid (ASIST) training offered to key workers; outreach support provided by trained and supervised MIC staff; state-wide suicide prevention hotline; case management service; and postvention support provided in the event of a suicide. Findings from over 7,000 workers (April 2008 to November 2010) are reported, indicating strong construction industry support, with 67% building sites and employers approached agreeing to participate in MIC. GAT participants demonstrated significantly increased suicide prevention awareness compared with a comparison group. Connector training participants rated MIC as helpful and effective, felt prepared to intervene with a suicidal person, and knew where to seek help for a suicidal individual following the training. Workers engaged positively with the after-hours crisis support phone line and case management. MIC provided postvention support to 10 non-MIC sites and sites engaged with MIC, but not yet MIC-compliant. Current findings support the potential effectiveness and social validity of MIC for preventing suicide in construction workers.